Aktivitas Antioksidan Senyawa Kumarin Ter-O-Geranilasi dari Akar Limonia acidissima L. - Tjitjik Srie Tjahjandarie; Ratih Dewi Saputri; Mulyadi Tanjung (Journal of Tropical Pharmacy and Chemistry, 2017)
Five O-geranylated coumarins namely as auraptene (1), 7-((2’E,6’E)-5’-hydroxy-3’,7’-dimethylocta-2’,6’-dienyloxy)coumarin (2), 7-(2’E,5’E)-7’-hydroxy-3’,7’-dimethylocta-2’,5’-dienyloxy) coumarin (3), 6-methoxy-7-oxygeranylcoumarin (4), and 8-oxygeranylpsoralen (5) were isolated from the roots of Limonia accidissima L. Their structures were determined based on spectroscopic data such as UV, IR, MS and NMR. Compounds 1–5 were evaluated for their radical scavenging against 2,2-diphenyl-1-picrylhydrazyl (DPPH), showing their IC50 were 462; 13; 260; 210 and 234 µg/ml, respectively. Keywords: Limonia accidissima L., O-geranylated coumarins, antioxidant activity, DPPH